Peningkatan Nilai Jual Biji Mete Hasil Produksi Masyarakat Desa Gumantar Kabupaten Lombok Utara - Ade Putra Kurniawan; Ferly Eka Kerniati; Andre Rachmat Scabra (Fakultas Pertanian Universitas Mataram, 2020)
Gumantar Village is one of the villages in North Lombok Regency which has quite good potential in the agriculture and plantation sectors. One of the agricultural products in Gumantar Village is Cashew seeds. The community of Gmumantar Village is not yet optimal in terms of cashew nut processing. Cashew seed products harvested through plantations are sold in raw condition to collectors. Penagbdian activities to the community aims to increase the sale value of processed cashew seed products in Gumantar Village, North Lombok Regency. The increase in selling value is done by processing cashew seeds into ready-to-eat food products. The method of activities carried out is by conducting surveys, training, assistance and evaluation. Partners in community service activities are community groups that are part of the